COMPARATIVE ANALYSIS IN THE AEROBIC RESISTENCE OF TEENAGERS WITHIN A SOCCER TRAINING PROGRAM OF SOCCER FIELD AND BEACH SOCCER (Fiep Bulletin - online, 2015)
Two groups with ages between 14 and 16 years old, Group A practices Beach Soccer and Group C practices Field Soccer. Both groups practice their sports modality for at least one year. From these subjects mentioned it intends to place in question the conflicts of playing Field Soccer and Beach Soccer in the development of the aerobic resistance in teenagers. Methodology: The characteristic of this present research is the comparative descriptive research of the field. Objective: identify using the Cooper track test 12 minutes of aerobic resistance on teenagers inserted in a Soccer Field Training Program within adolescents in a Beach Soccer training program clarifying the average of the maximum capacity of oxygen absorption of each group. Results: the Beach Soccer (Group A) got better results than the Field Soccer (Group C). The average distance for Group A was 2710 meters and for Group C was 2136 meters. Conclusion: From these results Group A was better than group C with 37, 7%. Just out of curiosity, a 12 minutes race test on the sand was given to see their performance .The average distance accomplished for Group A was 2105 meters and for group C was 1691, in another words, there was a difference of 37, 5% between them showing that the performance in percentile levels that they were very close in the track, as much as in the sand.
Keywords: Aerobic resistance; Soccer; Sports Training.